Near-Threshold Production of W±, Z0, and H0 at a Fixed-Target Experiment at the Future Ultrahigh-Energy Proton Colliders - J. P. Lansberg; R. Mikkelsen; U. I. Uggerhøj (Advances in High Energy Physics)
We outline the opportunities to study the production of the Standard Model bosons, W±, Z0, and H0, at “low” energies at fixed-target experiments based on possible future ultrahigh-energy proton colliders, that is, the High-Energy LHC, the Super proton-proton Collider, and the Future Circular Collider hadron-hadron. These can be indeed made in conjunction with the proposed future colliders designed to reach up to s=100 TeV by using bent crystals to extract part of the halo of the beam which would then impinge on a fixed target. Without disturbing the collider operation, this technique allows for the extraction of a substantial amount of particles in addition to serving for a beam-cleaning purpose. With this method, high-luminosity fixed-target studies at centre-of-mass energies above the W±, Z0, and H0 masses, s≃170–300 GeV, are possible. We also discuss the possibility offered by an internal gas target, which can also be used as luminosity monitor by studying the beam transverse shape.